Moderate Work Life Balance Enhances Employee Creativity At Work, But The Higher-Level Correlates Negatively As Employee Enters The Comfort Zone - Ãmmaar Baig , Syed Haider Tipu , Yousaf Khan , Ahmad Shujāã Baig (Migration Letters, 2024)
Work-life balance and creativity at work are gradually becoming pivotal for employee enhancement and offer strategic value to organizational achievements. This research discusses the concept that within the present competitive marketplace, organizations are required to establish work-life balance only to a moderate level, and optimize creativity at work for their valued workforce. The stratified sample included 44 participants from the HR department and 62 participants from the Marketing departments of both the companies. Results reveal grandeur influence (95.2%) of moderate work life balance upon employee creativity at work (R2=0.952). In addition, the statistical analysis discloses a negative correlation (- .208*) between higher levels of work life balance and creativity at work. Thus providing evidence that with higher levels of work life balance, the employee enters the ‘comfort zone’ and his/her creativity at work starts diminishing. This research will be valuable for HR professionals to preserve discipline within the organization.